Multi-platform diagnostic strategy and biosecurity as basis of contagious agalactia control programs in endemic areas - Christian De la Fe; Ana Grau; Olga Minguez; Antonio Sánchez; Rosario Esquivel; Juan C. Corrales (Irish Veterinary Journal)
Abstract Background Control strategies against contagious agalactia (CA), considered one of the most important diseases affecting small ruminants in countries surrounding the Mediterranean, are mainly based on traditional strategies considered suboptimal such as the use of inactivated vaccines and antibiotics. This manuscript analysed the efficacy of an alternative non-mandatory official control programme based on a multi-platform diagnostic panel and biosecurity developed and started in 185 herds placed in a contagious agalactia endemic area of Spain, using the data of 74,080 samples collected and analysed during a 4 years-period (2018–2021). Results Globally, the combined analyses of bulk tank milk (BTM), ear or nasal swabs (in goats or sheep, respectively) and the serology to detect Mycoplasma agalactiae (Ma), allowed the detection of 40.54% of positive farms (n = 75), with Ma the species always detected in sheep (100%) and Mycoplasma mycoides subsp. capri (Mmc, 68,8%), Ma (29,3%) or both of them (1,9%) in goats. Taking into account productive aptitude and vaccination against CA, the use of BTM, ear or nasal swabs, and serology for herd classification demonstrated either a lack of concordance or only weak concordance. In herds that did not vaccinate, the classification of positives by male serology or swab detection showed moderate concordance. Vaccination against AC proved to be a protective factor against the occurrence of herds with bucks or rams testing positive. Conclusions Since the different diagnostic techniques are not interchangeable, it is necessary to apply a multi-platform diagnostic panel for the accurate classification of herds. Based on official classification, strict biosecurity standards, including the prohibition of the entry of animals with unknown health status, allowed the completion of the CA control program.